Lunas sa unos the implementation of Metro Manila Development Authority?s (MMDA) Oplan Unos Campaign in Marikina - Dela Cruz, Ma. Alessandra Bañares; Gayosa, Aleth (2012)
"This thesis examines how OPLAN UNOS engage selected stakeholders, particularly planners, implementers and residents, in disaster preparedness. OPLAN UNOS is a campaign launched by the Metro Manila Development Authority in order to mitigate disaster and its following consequences. The study looks at the planning and management processes and communication efforts involved in OPLAN UNOS. It explores the awareness and knowledge of planners, implementers, and residents; and approaches their responses in terms of evaluation and practice. This thesis employs a qualitative approach through in-depth interviews with stakeholders and key informants. The implementation of OPLAN UNOS was primarily guided by an organizational structure wherein the MMDA relied on a specific subcommittee aside from already existing local government units and point persons. Conveyed through its different channels such as rescue tools, seminars, campaign paraphernalia and interpersonal exchanges, OPLAN UNOS especially enhances the awareness and involvement of its stakeholders; the latter became mindful of their duties and responsibilities during disasters. While encountered problems included hardheadedness of residents and lack of manpower and budget, OPLAN UNOS promoted changes that planners, implementers, and residents of Marikina deemed to have benefitted them."
Vita.
Undergraduate thesis (A.B. Communication Research)--University of the Philippines.
Keywords: OPLAN UNOS; Emergency management -- Philippines -- Marikina